Suitability of Groundwater in Basrah Province for Industrial, Construction and Agricultural Purposes - Dawood, Ammar S.; Abbas, Abdul Hussain A.; Alhasan, Zainab M. (Basrah Journal for Engineering Sciences, 2016)
This study aims to evaluate quality of groundwater samples in south of Basrah Province for industrial, construction and agricultural purposes. Groundwater samples were collected in summer season of the year 2015 from (29) wells located in different districts in Basrah province (Safwan, Zubair and Um- Qasir). The groundwater samples were analyzed for pH, electrical conductivity (EC), total dissolved solids (TDS) and other major ions. The chemical results indicate that the groundwater in the study area was unsuitable for industrial uses according to standard classification. Some other standard classification recommended that, the unsuitable groundwater could be used after treatment of some of its element while groundwater in study area may be used for construction purposes with suitable treatment of high ions concentration. After studying the factors that determine the suitability of groundwater for irrigation purpose such as pH, electrical conductivity, total dissolved solids, Sodium ratio(Na%) and sodium adsorption ratio (SAR). The groundwater in study area can be classify based on (EC) values, as unacceptable for irrigation except for very salt-tolerant plants and excellent drainage. According to other parameters like Na% and SAR , groundwater of the study area are classify as poor to very poor water and need for suitable treatment before using it.